2021
DOI: 10.1039/d0ra10698d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gd/N co-doped ZnO for enhanced UV-vis and direct solar-light-driven photocatalytic degradation

Abstract: The construction of a UV-Vis and direct sunlight functioning photocatalyst is a puzzling task for organic pollutant removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 31 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…The PL spectra of the prepared samples show three main peaks at 340, 380, and 466 nm. 49,50 We observed that the PL emission intensity of pure ZnO NPs was higher than those of Mo-ZnO NPs and Mo-ZnO/RGO NCs. A decrease in the emission intensity is allied with the hindrance of the recombination of charge carriers (e − /h + ), caused geometric distortions, and created more oxygen vacancies.…”
Section: Resultsmentioning
confidence: 87%
“…The PL spectra of the prepared samples show three main peaks at 340, 380, and 466 nm. 49,50 We observed that the PL emission intensity of pure ZnO NPs was higher than those of Mo-ZnO NPs and Mo-ZnO/RGO NCs. A decrease in the emission intensity is allied with the hindrance of the recombination of charge carriers (e − /h + ), caused geometric distortions, and created more oxygen vacancies.…”
Section: Resultsmentioning
confidence: 87%
“…After the nitridation at a higher temperature (>873 K), the O–H vibrations at around 3400 and 1600 cm –1 were barely observed, and CO 3 2– vibrations at around 1360 and 770 cm –1 disappeared due to the collapse of the layered structure and transformation to oxide species. The presence of O–Zn–N, Zn–N, and Al–N peaks at 1510, 1380, and 710 cm –1 confirms the incorporation of an N dopant into the oxide lattice. The Al–O vibration at 670 cm –1 was observed upon heating at 1073–1273 K, indicating the presence of ZnAl 2 O 4 .…”
Section: Resultsmentioning
confidence: 79%
“…After the nitridation at a higher temperature (>873 K), the O−H vibrations at around 3400 and 1600 cm −1 were barely observed, and CO 3 2− vibrations 33 at around 1360 and 770 cm −1 disappeared due to the collapse of the layered structure and transformation to oxide species. The presence of O−Zn−N, Zn−N, 37 and Al−N 38 Given the aforementioned results, we further investigated the local structure around Zn atoms in the nitridation products using XAFS, which can detect even small amounts of impurity phases because of its high sensitivity and element specificity. 39 The Zn−K edge X-ray absorption near edge structure (XANES) spectra of Zn−Al LDH changed after nitridation at temperatures greater than 773 K, indicating a transformation Notably, the spectra of samples nitrided at low temperatures (773−873 K) showed an absorption edge shoulder similar to that for Zn(CN 2 ) (Figure 4B).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Substances extracted from plants appeared as a very appropriate influencer for the extensive synthesis of alloy NPs else than various described procedures of using risky chemical compounds, causing severe damage if preserve in the environment. The plant material used also affects the consistency and flexibility of NPs [ 55 ]. More specifically, the use of peeled Solanum tuberosum common tuberous crop was suggested, because of the starch component; a major form of carbohydrate content could be proficiently utilized as a means for NP synthesis [ 56 ].…”
Section: The Followed Means Of Plant-derived Ag/zno Alloy Np Synthesismentioning
confidence: 99%